The genus Isotomodes Linnaniemi, 1907 of the Ibero-balearic fauna, with description of two new species (Collembola: Entomobryomorpha: Isotomidae) - Arbea, Javier (Zootaxa, 2006)
The genus Isotomodes Linnaniemi, 1907 is represented by 14 species in the Ibero-balearic fauna, two of which are new to the science. The two new Spanish species, Isotomodes rosae sp. nov. from Picos de Europa (Cantabria, Northern Spain) and Isotomodes rafaeli sp. nov. from Murcia (Southeastern Spain), are both here described. Drawings of the diagnostic structures of the new species and a key for the identification of Ibero-balearic species of Isotomodes are provided.